Structural investigation of mutant Mycobacterium smegmatis arylamine N-acetyltransferase: a model for a naturally occurring functional polymorphism in Mycobacterium tuberculosis arylamine N-acetyltransferase. - Kawamura, A; Sandy, J; Upton, A; Noble, M; Sim, E (2003)
Arylamine N-acetyltransferase (NAT) acetylates the front-line anti-tuberculosis drug isoniazid (INH) and has been identified in Mycobacterium tuberculosis. A naturally occurring single nucleotide polymorphism (SNP) was recently found in the NAT gene in clinical isolates of M. tuberculosis. The nucleotide change from G-->A (619) produces an amino acid change Gly(207) Arg, which appears to reduce the activity of the NAT from M. tuberculosis (TBNAT). It has not been possible to generate sufficient soluble recombinant TBNAT for 3D structural studies. Therefore, Mycobacterium smegmatis NAT (SMNAT), which has 60% identity to TBNAT and has Gly at 207, was used as a model to investigate the possible structural effects of the G-->A 619 SNP. The mutant form of SMnat (SM207Rnat) was constructed by in vitro site-directed mutagenesis and was heterologously expressed with an N-terminal His tag in Escherichia coli, for comparison with the SMNAT. Both recombinant SMNATs were purified using Ni affinity chromatography and treated with thrombin to cleave the tag. Both proteins were produced with average yields of over 10 mg/L and were active. Substrate specificity and thermal stability of SM207RNAT were assessed and compared with the wild type SMNAT using kinetic assays and circular dichroism spectroscopy. SM207RNAT was crystallised and a data set of 2.00 A resolution was obtained. The SM207RNAT had different substrate specificities to the wild type protein and the 3D structures revealed that the Gly(207) Arg mutation caused slight changes in the orientation of His(203) in SMNAT.